EXPLICIT AND IMPLICIT FACTORS, WHICH AFFECT THE COST OF CARGO TRANSPORTATION BY MARITIME TRANSPORT - Вишневська, Ольга; Вишневський, Дмитро (SWorldJournal, 2022)
This article considers a set of factors, which affect the cost of maritime transportation. Explicit and implicit factors, existing links between them, as well as an extent of influence of each of these factors on the cost of transportation were researched